Enhancing polyol/sugar cascade oxidation to formic acid with defect rich MnO2 catalysts - Yan, Hao; Liu, Bowen; Zhou, Xin; Meng, Fanyu; Zhao, Mingyue; Pan, Yue; Li, Jie; Wu, Yining; Zhao, Hui; Liu, Yibin; Chen, Xiaobo; Li, Lina; et al. (Nature communications, 2023)
Oxidation of renewable polyol/sugar into formic acid using molecular O 2 over heterogeneous catalysts is still challenging due to the insufficient activation of both O 2 and organic substrates on coordination-saturated metal oxides. In this study, we develop a defective MnO 2 catalyst through a coordination number reduction strategy to enhance the aerobic oxidation of various polyols/sugars to formic acid. Compared to common MnO 2 , the tri-coordinated Mn in the defective MnO 2 catalyst displays the electronic reconstruction of surface oxygen charge state and rich surface oxygen vacancies. These oxygen vacancies create more Mn δ+ Lewis acid site together with nearby oxygen as Lewis base sites. This combined structure behaves much like Frustrated Lewis pairs, serving to facilitate the activation of O 2 , as well as C–C and C–H bonds. As a result, the defective MnO 2 catalyst shows high catalytic activity (turnover frequency: 113.5 h −1 ) and formic acid yield (>80%) comparable to noble metal catalysts for glycerol oxidation. The catalytic system is further extended to the oxidation of other polyols/sugars to formic acid with excellent catalytic performance. This work develops defective MnO2 catalysts with Frustrated Lewis Pairs through a coordination number reduction strategy to enhance the aerobic oxidation of various polyols/sugars to formic acid.